2021
DOI: 10.56499/jppres20.927_9.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacist-led intervention on predictors of diabetic neuropathy at two different hospitals of Malaysia

Abstract: Context: Diabetes mellitus is a progressive disease. In poor glycemic control, it can cause severe and non-reversible complications. A proper educational intervention from health care providers is needed for patients to decrease the progression of diabetes and its complications. Aims: To evaluate the effect of pharmacist-led educational intervention on predictors of diabetic neuropathy in patients. Methods: From two tertiary care hospitals, diabetic patients were randomly selected and divided into the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…In this study, the PC process led to a signifcant increase in the number of patients toward the moderate zone (i.e., MNSI-HIS � 5-6) of improvement; however, complete improvement toward MNSI-HIS <4 has not been reported. Tis fnding is not consistent with a previous study conducted by Hayat et al in which a signifcant reduction in the signs and symptoms of DN was observed in the pharmacist's intervention group after one year of the study [48]. Tis discrepancy in results may be due to the shorter duration of the intervention in the present study.…”
Section: Discussioncontrasting
confidence: 97%
“…In this study, the PC process led to a signifcant increase in the number of patients toward the moderate zone (i.e., MNSI-HIS � 5-6) of improvement; however, complete improvement toward MNSI-HIS <4 has not been reported. Tis fnding is not consistent with a previous study conducted by Hayat et al in which a signifcant reduction in the signs and symptoms of DN was observed in the pharmacist's intervention group after one year of the study [48]. Tis discrepancy in results may be due to the shorter duration of the intervention in the present study.…”
Section: Discussioncontrasting
confidence: 97%
“…In this study, there was a notable proportion of patients potentially at risk of DPN who should be examined by a specialist to confirm the diagnosis of DPN. Accordingly, the study shows that pharmacist-led interventions using a simple, reliable, and non-invasive tool ( 16 , 18 , 19 ) can play a valuable role in screening and counseling diabetic patients about DPN and its risk factors. Since DPN affects a varying number of patients with diabetes (from 10% to 90%) ( 20 , 21 ), early diagnosis appears to be the best strategy in the care of the diabetic patient.…”
Section: Discussionmentioning
confidence: 96%